2015
DOI: 10.3892/ijo.2015.2900
|View full text |Cite|
|
Sign up to set email alerts
|

miRNA-1207-5p is associated with cancer progression by targeting stomatin-like protein 2 in esophageal carcinoma

Abstract: Newly discovered intrinsic regulators, the miRNAs regulate gene expression by binding to the 3'-untranslated regions of the genome. Accumulating studies have indicated that miRNAs are aberrantly expressed in various human cancers. We found that miRNA-1207-5p (miR‑1207-5p) was markedly downregulated in esophageal carcinoma (EC) tissues, and was correlated with EC differentiation, pathological stage and lymph node metastasis. Rates of apoptosis were increased and cell invasion ability was decreased in EC9706 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…reported that LncRNA BC032469 could competitively bind to miR‐1207‐5p to regulate hTERT expression and promote tumor suppression. Yang et al . showed that miR‐1207‐5p decreased the target gene STOML‐2 in esophageal cancer, which was related to the differentiation status and pathological stage of the tumor, as well as to the presence/absence of lymph node metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…reported that LncRNA BC032469 could competitively bind to miR‐1207‐5p to regulate hTERT expression and promote tumor suppression. Yang et al . showed that miR‐1207‐5p decreased the target gene STOML‐2 in esophageal cancer, which was related to the differentiation status and pathological stage of the tumor, as well as to the presence/absence of lymph node metastasis.…”
mentioning
confidence: 99%
“…L€ u et al (20) reported that LncRNA BC032469 could competitively bind to miR-1207-5p to regulate hTERT expression and promote tumor suppression. Yang et al (21) showed that miR-1207-5p decreased the target gene STOML-2 in esophageal cancer, which was related to the differentiation status and pathological stage of the tumor, as well as to the presence/absence of lymph node metastasis. Wu et al (22) reported that increased expression of miR-1207-5p in ovarian cancer promoted the transformation of tumor cells to stem cells by activating the Wnt/b-catenin pathway.…”
mentioning
confidence: 99%
“… 21 miR-1207-5p also influences tumor progression in esophageal carcinoma. 9 Therefore, based on the studies mentioned, we propose that miR-1207-5p may be a potential target in PGBC therapy, as well.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of noncoding RNAs that are 18–25 nucleotides in length and play important roles in various cellular processes, including proliferation, differentiation, metabolism, and apoptosis. 8 , 9 Previous studies have demonstrated that miRNAs expression varies in human cancers, such as esophageal cancer and colorectal cancer, and that these molecules function as tumor suppressors or oncogenes. 10 , 11 Among the miRNA families, miR-1207-5p is highly expressed in gastrointestinal cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation